Rancang Bangun E-Commerce Pusat Oleh-oleh Khas Kediri - Mufti Khalimi; Agus Pramono; Muhaji Bayu Suryawan (CAHAYAtech, 2020)
Web ¬E-commerce system is an application or software that is developed to promote Kediri’s original souvenirs, here we choose Toko Oleh Oleh Tahu Shinta Kediri as a subject. The problem that the store face now is from promoting way, they still use the conventional one, there have not been any online platform yet, and the information about Kediri’s souvenirs is limited as well. The goals of developing this E-commerce platform are to promotote Kediri’s original souvenirs without looking out the place, so that we make the ordering proccess easier to people from outside of Kediri. Besside that, this program could be one of the information system and publication, so everyone knows that Kediri has their own product. The method that we use in this developing is observatuin, literature review, and interview. This program is developed by using PHP programming language, with MySQL as the database. The design is builded with HTML, CSS, and Bootstrap framework. The result that is expected from these proccess is there will be a system that contaion information about Kediri’s original souvenirs and we can promote it widely, so more and more people will know that Kediri has their own souvernis which are a must to try.